2012
DOI: 10.1111/j.1468-5876.2012.00572.x
|View full text |Cite
|
Sign up to set email alerts
|

Market Structure and Privatization Policy Under International Competition*

Abstract: We investigate the relations among market structure, privatization, and tax‐subsidy policies. We find that if there is no foreign competitor, privatization does not matter under the optimal tax‐subsidy policy regardless of the number of firms. However, this is not true if there are foreign competitors; further, privatization is more likely to improve welfare when the number of firms is larger even under the optimal tax‐subsidy policy. We also investigate two Stackelberg models: public leadership and private le… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
15
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 34 publications
(16 citation statements)
references
References 45 publications
1
15
0
Order By: Relevance
“…These result can also be found in Matsumura and Tomaru (2012) and Lin and Matsumura (2012). The reason is as follows.…”
Section: The Modelsupporting
confidence: 60%
See 2 more Smart Citations
“…These result can also be found in Matsumura and Tomaru (2012) and Lin and Matsumura (2012). The reason is as follows.…”
Section: The Modelsupporting
confidence: 60%
“…18. Matsumura and Tomaru (2012) has a similar result that the optimal policy could be subsidy or tax; however, we further point out that whether a subsidy or a tax should be adopt is independent with the pubic firm's inefficiency level. 19.…”
Section: Notesmentioning
confidence: 83%
See 1 more Smart Citation
“…Wang and Lee (2013) introduced foreign firms into the framework of Ino and Matsumura (2010) showing that foreign ownership matters in Stackelberg models. Matsumura and Tomaru (2012) revisited the privatization neutrality theorem presented by White (1996) showing that his result does not hold under foreign ownership of the private firms. 9 Our result holds true even when multiple public firms exist.…”
Section: Modelmentioning
confidence: 99%
“…Several pioneering works (De Fraja and Delbono [1], Fjell and Pal [2], and Matsumura [3]) found that the privatization of public firms improves social welfare, and that it is optimal to partially privatize public firms. Furthermore, later studies extended these models in many directions and found several interesting results (see White [4], Payago-Theotoky [5], Kato and Tomaru [6], Matsumura and Tomaru [7], for example).…”
Section: Introductionmentioning
confidence: 99%